Knowledge and Happiness - Mizińska, Jadwiga (Sensus Historiae, 2024)
The present considerations have been inspired by the relationship existing between the two categories: “knowledge” and “happiness.” Both of them are quite ambiguous, so it is our aim to examine their mutual relationship. The departure point will be the treatise On Happiness and Memories by Władysław Tatarkiewicz. We are particularly interested in differentiating “emotions” and “feelings,” as well as in the term of “emotional intelligence” and the deviations of the latter defined as moral insanity and resentment. The main thesis of the present article is that Znaniecki’s ideal, i.e. “the well-behaved man,” as opposed to “the primitive man,” fulfils the conditions for the harmonious development of feelings, rationality and self-awareness. He can function on the meta-level, so he has the ability of self-criticism. However, the most important factor is the attitude towards other people and to oneself.